Semiotika Istilah Arab Akad Waḍī'ah Yad al-Ḍamānah pada Produk Penghimpunan Dana Bank Syariah - Hendri Hermawan Adinugraha; Ana Kadarningsih; Godham Eko Saputro (Islamica: Jurnal Studi Keislaman, 2018)
The purpose of this research is to know the impact and result of Arabic term semiotics on Waḍī'ah Yad al-Ḍamānah contract. The result of the research shows that after the experiment conducted through the training in the classroom, the comprehension ability of the respondents to the Arabic term semiotization experiment on the Waḍī'ah Yad al-Ḍamānah contract as one of Islamic bank fundraising products has increased significantly with an average achievement up to 78 percent. Based on observations and interviews, the most preferred by respondents was symbolic method in facilitating the understanding of Arabic terms on Waḍī'ah Yad al-Ḍamānah contract. The reason is because the information transformation is more simple, solid, and clear. Symbolic method through the media sign or picture of gift and ribbon presumably can be creative innovation in comprehending the Arabic terms contained in Waḍī'ah Yad al-Ḍamānah contract.